Radiation-induced basal cell carcinoma - Omid Zargari (Mattioli1885, 2015)
Background: The treatment of tinea capitis using radiotherapy was introduced at the beginning of the twentieth century. A variety of cancers including basal cell carcinoma (BCC) are seen years after this treatment.